STUDENT WORKSHEET BASED ON SETS IN ARCHAEBACTERIA AND EUBACTERIA TOPICS TO TRAIN CRITICAL THINKING ABILITY FOR TENTH GRADE - Dewi, Novi Nurmala; Trimulyono, Guntur (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
The purposes of this research were to produce valid student worksheets based on SETS in Archaebacteria and Eubacteria topics to train critical thinking ability for tenth grade. The validity evaluated from several criteria, which are presentation, content, language, and suitable of task in worksheet with critical thinking indicators. The methods of this research is 4-D consisting of define, design, develop, and disseminate but disseminate didnâ€™t occur.Â Limited trial was done by 16 students in SMAN 1 Sidoarjo. Based on the validator assessment and the result of limited tested, the worksheet developed got percentage as follows: content criteria got modus 4 categoried valid, presentation criteria got modus 4 categoried valid, language criteria got modus 4 categoried valid, and suitable task in worksheet with critical thinking indicators got modus 1 categoried valid. This things supported by the result test average that there are 75% of student thorough posttest and also the student respon got 92% positive respon for the worksheet. Based on the result above, so that the student worksheet is valid to use.Keywords: Development of worksheet, SETS, Archaebacteria and Eubacteria, Critical Thinking Skill.